2006
DOI: 10.1007/s11434-006-2155-4
|View full text |Cite
|
Sign up to set email alerts
|

Doping effects of ZrC and ZrB2 in the powder-in-tube processed MgB2 tapes

Abstract: We have investigated the effects of ZrC and ZrB 2 doping on the superconducting properties of the powder-in-tube processed MgB 2 /Fe tapes. Samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM/EDX), transport and magnetic measurements. We confirmed the following quite different roles of ZrC and ZrB 2 in MgB 2 . ZrC doping was found to decrease the transport critical current density (J c ) at 4.2 K, while the critical temperature (T c ) kept constant. In contrast, the J c val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The effect of metal carbides like ZrC [45], NbC [46], TaC and MoC 2 [47] has been studied in our group. We found that these carbides show little effect on J c , because they are stable in contact with Mg and B even at high temperature; thus no fresh reactive C is available for incorporating into the MgBB 2 lattice during its formation.…”
Section: Carbon Dopingmentioning
confidence: 99%
“…The effect of metal carbides like ZrC [45], NbC [46], TaC and MoC 2 [47] has been studied in our group. We found that these carbides show little effect on J c , because they are stable in contact with Mg and B even at high temperature; thus no fresh reactive C is available for incorporating into the MgBB 2 lattice during its formation.…”
Section: Carbon Dopingmentioning
confidence: 99%
“…ZrB 2 additions, which have the same crystal structure as MgB 2 , were previously studied [14]- [17]. In situ powder-in-tube (PIT) method and heat treatment at 600 • C for 40 min [14], [15], and In situ method followed by swaging, wire drawing, rolling into tapes, and heat treatment at 800 • C for 1 h [16], were used to fabricate MgB 2 + ZrB 2 tapes. Milling mixtures of powders in a SPEX mill for 48 min, pressing into cylindrical pellets in a steel Manuscript die, and heat treating at 700 to 900 • C for 1 h are some steps used to produce MgB 2 +ZrB 2 pellets [17].…”
Section: Introductionmentioning
confidence: 99%
“…Desde a descoberta de supercondutividade no MgB 2 , muitos grupos de pesquisa (CAVA;ZANDBERGEN;INUMARUA, 2003;CANFIELD et al, 2001) (AGATSUMA et al, 2006;YAMAMOTO et al, 2005;WILKE et al, 2004;DOU et al 2003;DOU et al, 2002), devido a uma possível substituição nos sítios de boro pelos átomos de carbono na estrutura cristalina do MgB 2 (MAZIN et al, 2002). Com isso, alguns grupos de pesquisa têm analisado diversos materiais como fonte de carbono: carbono puro (MA, 2006;SOLTANIAN et al, 2003a), grafite (SENKOWICZ et al, 2005XU et al, 2004a), nanotubos de carbono (SERRANO et al, 2008;SERQUIS et al, 2007;YEOH et al, 2004;SERQUIS et al, 2003, DOU et al, 2002a), diamante (ZHAO et al, 2003), carbono nanohorns (BAN et al, 2005), carbeto de silício (VINOD et al, 2009;SERRANO et al, 2008;AGATSUMA et al, 2006;SOLTANIAN et al, 2005;DOU et al, 2002) e mais recentemente os compostos orgânicos (ZHANG et al, 2009;KIM et al, 2006;YAMADA et al, 2006).…”
Section: Dopagem Do Mgbunclassified